The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1088/1361-6528/28/4/045707
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of electrically active defects in InGaAs quantum wire intermediate-band solar cells using deep-level transient spectroscopy technique

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Hence, for devices based on light absorption, a different structure design should be considered. We believe, such an improvement is necessary to be suggested because many research groups consider si -GaAs substrate as a basis for novel p - n -type both QD infrared photodetectors [ 11 13 ] and solar cells [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hence, for devices based on light absorption, a different structure design should be considered. We believe, such an improvement is necessary to be suggested because many research groups consider si -GaAs substrate as a basis for novel p - n -type both QD infrared photodetectors [ 11 13 ] and solar cells [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…thicker MBs or defect control strategies [28,29,87]) allowing to suppress strain-related defects generated near the QD layer and substrate/MB interface should be used. Simultaneously, the in-depth analysis of the effect of growth parameters on structural defects in multilayer stacks of QD is highly desirable [70,88]. We expect that these results and outcomes could foster further development of IR light-emitting devices based on InAs QDs embedded in In x Ga 1-x As layers with high percentages of indium.…”
Section: Time-dependent Pcmentioning
confidence: 96%
“…However, the above techniques allow to visualize only extended defects without information about the associated trap level states. Unlike the GaAs-based QD structures, highly investigated earlier [17][18][19][20][21][22][23], at present there are only a few photoelectric studies of defects in metamorphic In(Ga) As/InGaAs ones. DLTS spectra of InAs/In 0.15 Ga 0.85 As QD structures by Rimada et al [24] have shown two peaks associated with point defects (PDs) along with two bands associated with extended defects related to threading dislocations and V-shaped defects generated, respectively, at the lower InGaAs/GaAs interface [25] and in the QD plane [25,26].…”
Section: Introductionmentioning
confidence: 99%